2005
DOI: 10.1159/000086909
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities in sperm from infertile men with normal somatic karyotypes: oligozoospermia

Abstract: Recently, intracytoplasmic sperm injection (ICSI) has been extremely successful for the treatment of male infertility. However, transmission of cytogenetic defects to offspring is a great concern. There are two types of cytogenetic problems in patients seeking ICSI; one is the transmission of genetic defects from patients with constitutional chromosomal abnormalities and the second is the generation of de novo defects in infertile men. Generally about 5.1% of infertile men have chromosomal abnormalities. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
2
27
1
2
Order By: Relevance
“…Alternatively, the presence of abnormal seminal parameters was also considered because an association between low semen quality and increased tax of aneuploid sperm has been described. 31,[42][43][44] In this sense, a recent study (Sarrate et al, unpublished results) has revealed a 14% incidence of this phenomenon in individuals with altered seminal parameters and a normal karyotype. Nevertheless, in the population of reciprocal translocation carriers analyzed in this work, the frequency of cases with increased percentages of aneuploidies rose to 50%.…”
Section: Interchromosomal Effectmentioning
confidence: 93%
“…Alternatively, the presence of abnormal seminal parameters was also considered because an association between low semen quality and increased tax of aneuploid sperm has been described. 31,[42][43][44] In this sense, a recent study (Sarrate et al, unpublished results) has revealed a 14% incidence of this phenomenon in individuals with altered seminal parameters and a normal karyotype. Nevertheless, in the population of reciprocal translocation carriers analyzed in this work, the frequency of cases with increased percentages of aneuploidies rose to 50%.…”
Section: Interchromosomal Effectmentioning
confidence: 93%
“…However, it cannot be excluded that CCR carriers are more prone to exhibit ICE because of the substantially high numbers of chromosomes involved in rearrangement, especially with regard to the ongoing debate on the influence of chromosomal rearrangements on the proper meiotic behaviour of other chromosomes. It has also been documented that increased aneuploidy rates can be present in spermatozoa of males with decreased sperm seminological parameters (OAT -oligo-, astheno-, teratozoospermia) (Hristova et al 2002, Tempest & Griffin 2004, Machev et al 2005, Miharu 2005, Rives 2005, Tang et al 2010. A large majority of findings indicate a well-defined link between ICE presence and oligozoospermia, while no such clear association has been observed in cases of astheno-or teratozoospermia (Tempest & Griffin 2004, Machev et al 2005, Miharu 2005, Rives 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established a link between semen parameter alteration and sperm aneuploidy rate (Calogero et al, 2001;Templado et al, 2002;Miharu, 2005;Collodel et al, 2007;Li et al, 2008;Martin, 2008;Perrin et al, 2008) . Moreover, the severity of semen alteration has been suggested to positively affect the frequency of chromosomal aneuploidy (Martin et al, 2003;Rodrigo et al, 2004;Gianaroli et al, 2005;Mehdi et al, 2006;Faure et al, 2007).…”
mentioning
confidence: 99%